THE SOCIAL-PHILOSOPHICAL ANALYSIS OF RESPONSIBILITY IN A GLOBALIZED WORLD - Сабадуха, О. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Researched problem of responsibility in European social philosophy of age of Post modern in the context of peculiarities of present globalized world.